Ella Bella ballerina and Swan lake - Mayhew, James, 1964- (Hauppauge, NY : Barron's, 2011)
Ella Bella's ballet teacher is preparing the class for their performance of "Swan Lake" and Ella dreams of dancing the lead and meeting all the characters in the ballet.
4.5
K-3
K-3
Keywords: Swan lake (Choreographic work) -- Juvenile fiction; Swan lake (Choreographic work) -- Fiction; Swan lake (Choreographic work) -- Fiction; Ballerinas -- Juvenile fiction; Music box -- Juvenile fiction; Ballerinas -- Fiction; Music box -- Fiction; Ballerinas -- Fiction; Music boxes -- Fiction; Picture books for children